AN INTEGRATED NURSING EDUCATION MODEL FOR TUBERCULOSIS PREVENTION AND ENVIRONMENTAL SANITATION IMPROVEMENT THROUGH COMMUNITY-BASED TOTAL SANITATION (STBM) - Vendi Eko Kurniawan; Ismaildin Ns.; Kiki Febrianto; Bagus Sulianto (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2026)
Background: Tuberculosis (TB) remains a major public health problem in Indonesia, where household environmental conditions, sanitation quality, and limited community awareness strongly influence transmission. Strengthening TB prevention requires integrated approaches that combine biomedical, behavioral, and environmental health strategies. The Community-Based Total Sanitation (STBM) program, alongside Contact Investigation (CI) and Tuberculosis Preventive Therapy (TPT), presents an opportunity for comprehensive community-level intervention. Objectives: This study aimed to evaluate the effectiveness of an integrated nursing education model combining clinical TB education, CI, TPT counselling, and STBM-based sanitation triggering in improving knowledge, hygiene practices, and environmental sanitation among TB-affected households in Jombang Regency. Methods: A quasi-experimental one-group pre–post design was conducted with 48 participants recruited purposively from households of active TB patients and at-risk community members. The intervention included structured TB education, symptom-based CI screening, TPT counselling, and participatory STBM triggering. Knowledge was assessed using a validated questionnaire, while hygiene behaviors and household sanitation conditions were evaluated through structured observations. Data were analysed using paired t-tests, McNemar tests, and effect size calculations. Results: Knowledge scores increased significantly from a mean of 54.76 to 74.67 (p < 0.001) with a very large effect size (Cohen’s d = 2.07). Hygiene practices, particularly handwashing with soap at critical times, showed significant improvement (p < 0.001). Environmental sanitation indicators, including improved latrine ownership and enhanced household ventilation, also demonstrated positive changes after the intervention. Conclusion: The integrated nursing education model effectively improved knowledge, hygiene behavior, and environmental sanitation among participants, demonstrating strong potential as a community-based TB prevention strategy. Although limited by the absence of a control group and a short follow-up period, the model is suitable for adoption in primary healthcare programs to strengthen holistic TB control efforts.